2013
DOI: 10.1007/s40264-013-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Proton Pump Inhibitor Use is Associated with Vascular Calcification in Chronic Kidney Disease: A Cross-Sectional Study Using Propensity Score Analysis

Abstract: In haemodialysis patients, long-term treatment with PPIs, especially in the presence of warfarin treatment, is associated with vascular calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Possible reasons included that kidney became more vulnerable to the damage of interstitial inflammation with age, and the multiple drug (especially including PPI combined with other nephrotoxic agents) was more commonly used in the elderly . Additionally, cross‐section study indicated that PPI therapy significantly increased the risks of vascular calcification and pneumonia in CKD patients . Therefore, particular caution should be taken when prescribing PPI in the elderly and CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons included that kidney became more vulnerable to the damage of interstitial inflammation with age, and the multiple drug (especially including PPI combined with other nephrotoxic agents) was more commonly used in the elderly . Additionally, cross‐section study indicated that PPI therapy significantly increased the risks of vascular calcification and pneumonia in CKD patients . Therefore, particular caution should be taken when prescribing PPI in the elderly and CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, PPI use increased with age; its prevalence among patients over 60 years old reaching 14.0% in men and 16.3% in women and exceeding 20% among patients aged ≥80 years . In stage 5D chronic kidney disease (CKD) patients, we found that PPI use is even higher, with 76% of patients receiving long‐term treatment . Bone and mineral disorders, including secondary hyperparathyroidism and bone fractures, are more common among CKD patients than in people with normal renal function .…”
Section: Introductionmentioning
confidence: 99%
“…(5) In stage 5D chronic kidney disease (CKD) patients, we found that PPI use is even higher, with 76% of patients receiving long-term treatment. (6) Bone and mineral disorders, including secondary hyperparathyroidism and bone fractures, are more common among CKD patients than in people with normal renal function. (7) In the general population, PPI use is associated with an increased risk of fractures.…”
mentioning
confidence: 99%
“…Third, we could not show the efficacy of prophylactic low‐dose PPI in patients with previous UGIB (who are at the highest risk) due to our exclusion criteria. Fourth, several studies have suggested a relationship between impaired bone metabolism, fractures, vascular calcification, and PPIs . However, we did not assess long‐term adverse effects of PPI use in CKD patients because we did not assess vascular calcification, mineral bone disease states, and bone fractures.…”
Section: Discussionmentioning
confidence: 99%